2022
DOI: 10.3389/fgene.2022.1021770
|View full text |Cite
|
Sign up to set email alerts
|

Construction of m7G subtype classification on heterogeneity of sepsis

Abstract: Sepsis is a highly heterogeneous disease and a major factor in increasing mortality from infection. N7-Methylguanosine (m7G) is a widely RNA modification in eukaryotes, which involved in regulation of different biological processes. Researchers have found that m7G methylation contributes to a variety of human diseases, but its research in sepsis is still limited. Here, we aim to establish the molecular classification of m7G gene-related sepsis, reveal its heterogeneity and explore the underlying mechanism. We … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 48 publications
(49 reference statements)
0
1
0
Order By: Relevance
“…A previous study has shown that NCBP2 can mediate gene interactions to modify neurodevelopmental defects of the 3q29 deletion ( 52 ). Additionally, nudix hydroxylases (NUDTs) belong to the versatile, widely distributed, housecleaning enzyme family to catalyze the hydrolysis of a wide range of nucleoside pyrophosphates linked to amino acids ( 53 , 54 ). Furthermore, previous researches have reported that NUDT10 expression is associated with malignant behaviors of gastric cancer by promoting tumor cell invasion and a poor prognosis ( 55 , 56 ), whereas NUDT11 has been shown to be associated with longer survival period in liver cancer ( 57 ) and bladder cancer ( 58 ).…”
Section: Discussionmentioning
confidence: 99%
“…A previous study has shown that NCBP2 can mediate gene interactions to modify neurodevelopmental defects of the 3q29 deletion ( 52 ). Additionally, nudix hydroxylases (NUDTs) belong to the versatile, widely distributed, housecleaning enzyme family to catalyze the hydrolysis of a wide range of nucleoside pyrophosphates linked to amino acids ( 53 , 54 ). Furthermore, previous researches have reported that NUDT10 expression is associated with malignant behaviors of gastric cancer by promoting tumor cell invasion and a poor prognosis ( 55 , 56 ), whereas NUDT11 has been shown to be associated with longer survival period in liver cancer ( 57 ) and bladder cancer ( 58 ).…”
Section: Discussionmentioning
confidence: 99%
“…3 ). In m7G-associated molecular subtypes of sepsis, subtypes with higher amino acid metabolism activity are characterized by more abundant activated macrophages, M0 and NK cells, and higher expression of immune regulatory genes [ 191 ]. Not only is RNA methylation able to regulate multiple types of amino acid metabolism, but conversely, amino acid metabolism plays a critical role in RNA methylation [ 70 ].…”
Section: Classification Of Rna Methylationmentioning
confidence: 99%